Intracoronary and peripheral blood levels of TNF-like Cytokine 1A (TL1A) in patients with acute coronary syndrome. Issue 22 (29th May 2020) - Chen, Xinjing; Guo, Yansong; Lai, Li; Zhang, Shengli
Abstract: Background: TNF-like cytokine 1A (TL1A) is a subgroup of the tumor necrosis factor superfamily that exerts pleiotropic effects on cell proliferation, inflammation, activation, and differentiation of immune cells. The purpose of the current study is to investigate the clinical significance of TL1A expression in coronary and peripheral blood of patients with acute coronary syndrome (ACS) to determine if TL1A levels can serve as an accurate prognostic indicator. Methods: A total of 141 patients undergoing coronary angiography were divided into 4 groups: Control (n = 35), Unstable Angina (UA) (n = 35), acute non-ST segment elevation myocardial infarction (NSTEMI) (n = 37), and acute ST segment elevation myocardial infarction (STEMI) (n = 34). The levels of TL1A, MPO, hs-CRP, and IL-10 were detected in coronary and peripheral blood using enzyme linked immunosorbent assay (ELISA), and the MACE incidence rates were compared during 26.3 months of follow-up. Results: TL1A levels were not significantly different between the UA group and control group. In the UA group, TL1A levels were not significantly different between coronary blood and peripheral blood. However, TL1A levels were higher in the STEMI and NSTEMI groups than in the control group ( P  < .05). Moreover, TL1A levels in the coronary blood of the STEMI and NSTEMI groups were higher than in the peripheral blood ( P  < .05). The expression of TL1A in the coronary blood was the highest in the STEMI group. In addition, TL1A level in the coronary blood was highly correlated with levels in the peripheral blood (correlation coefficient: 0.899, P  < .001). The hs-CRP and MPO levels in the coronary and peripheral blood of all the UA, NSTEMI, and STEMI groups were higher than the control group. Plasma IL-10 levels in all the UA, NSTEMI and STEMI groups were lower than those in the control group. Plasma TL1A level was positively correlated with the cTnI level, degree of coronary thrombus burden, occurrence of slow coronary flow / no coronary reflow and MACE, but negatively correlated with the IL-10 level or non-correlated with the Syntax score. Conclusion: Plasma TL1A concentration levels can be used as a predictor of inflammatory response and prognosis in patients with ACS. Trial Registration: ClinicalTrials.gov, number: NCT02430025; Unique Protocol ID: FJPH20150101; Brief Title: Fujian Province Cardiovascular Diseases Study (FJCVD)